A preliminary study on drug switching strategy for second-line therapy after combination treatment of tyrosine kinase inhibitors and immune checkpoint inhibitors for unresectable hepatocellular carcinoma - Guan, Renguo; Yu, Chengyou; Li, Shaohua; Mei, Jie; Wei, Wei; Guo, Rongping (Frontiers in Pharmacology, 2022)
Background: Combination treatment with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) has been widely used in patients with unresectable hepatocellular carcinoma (uHCC). As no standard guidelines exist for second-line therapy after failure of combination treatment, this study aimed to determine a better drug-switching strategy. Methods: A total of 785 patients with uHCC who initially received a combination treatment of TKIs and ICIs between January 2017 and December 2021 at our center were screened. After applying the inclusion and exclusion criteria, a total of 102 patients were included in the study. Based on drug switching strategy, patients were divided into a single drug-switching group (A group, n = 49) and a double drug-switching group (B group, n = 53). The comparative effectiveness between groups A and B was assessed based on treatment response and survival time. Second progression-free survival (SPFS) and overall survival (OS) were compared using the Kaplan-Meier method and log-rank test. Results: Compared to group B, group A had a higher overall response rate (16.3% vs. 3.8%; p = 0.0392) and disease control rate (61.2% vs. 49.1%; p = 0.238). The median SPFS in group A was longer than that in group B (5.47 vs. 3.8 months; HR = 1.70, p = 0.0176). In the second-line therapy, the inclusion of lenvatinib resulted in a better SPFS than other TKI treatments (5.53 vs. 2.83 months, p = 0.0038). Conclusion: After the failure of the combination treatment of TKIs and ICIs, single-drug switching significantly prolonged median SPFS in uHCC patients, and retaining lenvatinib resulted in the survival benefit of single-drug switching.